Black Soundscapes White Stages : The Meaning of Francophone Sound in the Black Atlantic - Hill, Edwin C., 1971- (Book collections on Project MUSE., 2013)
A look at the dynamic role of sound in the culture of the African Diaspora as found in poetry, film, travel narratives, and popular music. This book explores the role of sound in understanding the African Diaspora on both sides of the Atlantic, from the City of Light to the islands of the French Antilles. From the writings of European travelers in the seventeenth century to short-wave radio transmissions in the early twentieth century, the author uses music, folk song, film, and poetry to listen for the tragic cri nègre. Building a conceptualization of Black Atlantic sound inspired by Frantz Fanon's pioneering work on colonial speech and desire, the author contends that sound constitutes a terrain of contestation, both violent and pleasurable, where colonial and anti-colonial ideas about race and gender are critically imagined, inscribed, explored, and resisted.